The simplest amino-borane H2 B=NH2 trapped on a rhodium dimer: pre-catalysts for amine-borane dehydropolymerization - Kumar, A; Beattie, NA; Pike, SD; Macgregor, SA; Weller, AS (Wiley, 2016)
The μ-aminoborane complexes [Rh2(LR)2(μ–H)(μ–H2B=NHR')][BArF4] (LR = R2P(CH2)3PR2; R = Ph, iPr; R' = H, Me) form by addition of H3B·NMeR'H to [Rh(LPh)(η6–C6H5F)][BArF4]. DFT calculations demonstrate that the aminoborane interacts with the Rh centers through strong Rh–H and Rh–B interactions. Mechanistic investigations show that these dimers can form via a boronium–mediated route; and are precatalysts for amine–borane dehydropolymerization, suggesting a possible role for bimetallic motifs in catalysis.